BEBERAPA PERMASALAHAN DAN PENGEMBANGAN METODE PERTANGGALAN RADIOKARBON - Wisjachudin, Faisal; Taftazani, Agus; Wasito, Bangun (BRIN, 1997)
Experimental works on a research and development of radiocarbon dating have been carried out. On this occasion several problems have to be concerned. These problems include a sampling technique. its handling in the laboratory, the existence of standard reference material contamination, isotopic fractionation , radiocarbon (14C) fluctuation, limitation of samples and data evaluation. In order to solve these problems. there have been established research which applied an improvement technique treatment techniques that regarded the caution of the problems. The experimental results on wood samples which washed and unwashed showed an age differences of 391 years from its true age of about 700 years ago. Delta 13C correction, due to the availability of isotopic fractionation. shows quite significant to be applied to sample having an age of under 30,000 years. A tree ring correction is a correction due to the existence of their previous radiocarbon dating fluctuation was also giving a correction that need to be studied by archaeologist . For that purpose, there was required a better handling better treatment of the samples.